The role of the B cells in the adoptive transfer of collagen-induced arthritis from DBA/1 (H-2q) to SCID (H-2d) mice. - Taylor, P; Plater-Zyberk, C; Maini, R (1995)
Collagen-induced arthritis (CIA) can be transferred from DBA/1 to SCID mice when native type II collagen (CII) is administered together with spleen cells, arthritis appearing some 14 days after cell transfer. In the present study, we demonstrate that both donor T- and B-lymphocyte populations play a role in this model, and that arthritis arises in SCID recipients of either murine or bovine native CII. Furthermore, the requirement for administration of soluble native CII can be replaced by subarthritogenic doses of serum from Wistar rats with CIA. In this case a fully developed arthritis appears as early as 2 days after cell transfer. However, protein G-purified IgG from CIA rat serum together with splenocytes from arthritic DBA/1 mice does not transfer arthritis. A key role of B cells in this model appears to be the production of a humoral arthritogenic factor since arthritis can be successfully transferred to SCID mice by CIA rat serum administered together with a B cell-depleted splenocyte population consisting of T cells and donor-histocompatible antigen-presenting cells. By contrast, transfer of disease cannot be achieved by co-administration of CIA rat serum and purified donor T cells, indicating that the presence of donor antigen-presenting cells is a requirement for adoptive transfer of arthritis. We propose that joint damage initiated by arthritogenic product(s) of the B cell lineage releases soluble antigens that are presented to T cells which perpetuate the disease. The finding that arthritis can be generated in SCID recipients of CIA rat serum together with splenocytes from non-arthritic DBA/1 mice immunized with denatured CII supports the hypothesis that T cells with specificity for denatured joint components perpetuate disease initiated by humoral factors.